Sensors: Development of a Highly Selective, Sensitive, and Fast Response Upconversion Luminescent Platform for Hydrogen Sulfide Detection (Adv. Funct. Mater. 2/2016). (January 2016) - Peng, Juanjuan; Teoh, Chai Lean; Zeng, Xiao; Samanta, Animesh; Wang, Lu; Xu, Wang; Su, Dongdong; Yuan, Lin; Liu, Xiaogang; Chang, Young‐Tae
Abstract : Hydrogen sulfide is regarded as one of the most significant gas signaling molecules for a variety of physiological and pathological processes. On page 191, L. Yuan, Y.‐T. Chang, and co‐workers design a H2 S sensing nanoplatform based on dye assembled upconversion nanoparticles. These powerful sensors demonstrate highly selective and rapid responses to H2 S in vitro and in cells, for a variety of applications in environmental and bioimaging fields.